2021
DOI: 10.1111/jfpp.16086
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and purification of bioactive peptides from yogurt whey: Application as a natural preservative in a model food system

Abstract: Bioactive peptides are specific sequences of amino acids and remain inactive as long as they bind to other amino acids in the original structure of protein (Harnedy & Fitz Gerald, 2012). Bioactive peptides may be released in the body of a living organism during digestion, enzymatic hydrolysis of food, or processing of food products such as fermentation, germination, and ripening (Moller et al., 2008).Bioactive peptides are mainly derived from plant and animal protein sources. Plant sources of bioactive peptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
0
5
1
Order By: Relevance
“…The IC 50 of the ABTS radical scavenging activity of hydrolysate protein from Pyropia columbina seaweed was reported 2.2 ± 0.1 g/L indicating the better ability of hydrolysate protein from S. ilicifolium (Cian et al, 2015). Differences in the results of the present study with some studies in terms of antioxidant activity of various peptides are influenced by factors such as amino acid composition, structure, molecular weight, and peptides size (Hajfathalian et al, 2018; Karimi et al, 2021; Mahdavi Yekta et al, 2020). In the study of Zhang et al, the antioxidant activity of fractionated bioactive peptides from protein hydrolysate of marine alga Gracilariopsis lemaneiformis with different molecular weights (<3, 3–10, and > 10 kDa) was investigated.…”
Section: Resultscontrasting
confidence: 89%
See 2 more Smart Citations
“…The IC 50 of the ABTS radical scavenging activity of hydrolysate protein from Pyropia columbina seaweed was reported 2.2 ± 0.1 g/L indicating the better ability of hydrolysate protein from S. ilicifolium (Cian et al, 2015). Differences in the results of the present study with some studies in terms of antioxidant activity of various peptides are influenced by factors such as amino acid composition, structure, molecular weight, and peptides size (Hajfathalian et al, 2018; Karimi et al, 2021; Mahdavi Yekta et al, 2020). In the study of Zhang et al, the antioxidant activity of fractionated bioactive peptides from protein hydrolysate of marine alga Gracilariopsis lemaneiformis with different molecular weights (<3, 3–10, and > 10 kDa) was investigated.…”
Section: Resultscontrasting
confidence: 89%
“…This difference in the antibacterial activity of peptides isolated from different natural sources can be influenced by some parameters such as different methods of peptide isolation and the method to used evaluated antimicrobial activity (Roy et al, 2020). In addition, according to previous studies, the amino acid composition, molecular weight of peptides, secondary structure, and charge distribution are other factors affecting the antimicrobial activity of peptides (Karimi et al, 2021; Roy et al, 2020). According to reports, the molecular weight of antimicrobial peptides is usually less than 10 kDa, which is in line with the molecular weight of hydrolysate protein from S. ilicifolium (Sharma et al, 2017).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The content and sequence of amino acids, as well as their structure, seem to alter following 21 days of storage due to the drop in pH and syneresis of yogurt, and it no longer has the original cohesiveness, lowering antioxidant activity. Karimi et al ( 2022 ) studied the impact of adding bioactive peptides produced from yogurt whey on the antioxidant activity of doogh (Iranian fermented dairy drink), finding that as the content of bioactive peptides increases, so does the antioxidant activity of doogh. Doogh's antioxidant activity is also diminished during storage.…”
Section: Resultsmentioning
confidence: 99%
“…The addition of bioactive peptides to yogurt and dairy products has been studied. The impact of adding bioactive peptides derived from yogurt whey to doogh was explored by some researchers who found that the quantity of inoculated harmful bacteria drops dramatically during storage (Karimi et al, 2021 ). Oliveiralima et al ( 2021 ) studied the impact of adding fish protein hydrolysate to yogurt and found that the antioxidant activity of the yogurt was boosted, as well as the product's physicochemical attributes.…”
Section: Introductionmentioning
confidence: 99%